Frail Patients Benefit From Less Invasive Procedures - Elke Stenvers MD; Riemke C. Mars MD; Rutger G. Zuurmond MD, PhD (Geriatric Orthopaedic Surgery & Rehabilitation, 2019)
Purpose: A traumatic periprosthetic fracture (PPF) is a long-term complication of total hip arthroplasty. Treatment options include revision, open reposition and internal fixation (ORIF), and minimally invasive techniques (MITs). To select the optimal surgical procedure, the level of frailty has to be considered, especially in patients with geriatric trauma. The aim of this study is to determine whether a frail patient has a better outcome postoperatively after less invasive treatment. Methods and materials: Sixty-three patients with an PPF were analyzed in this retrospective study. The level of frailty was obtained by the complex fracture frailty index (CFFI). The CFFI combines comorbidities, laboratory tests, physical abilities, social factors, and cognitive functions. Primary outcomes in this study include mortality, minor complications, and 3 major complications (deceased, reoperation or immobility after 1 year). Results: Thirty frail patients had lower survival rates ( P = .014) and significantly more major complications with a relative risk of 3.7 ( P = .02). In the entire group of 63 patients, there were no significant differences detected in the outcome measures; however, when specified in a subgroup of 30 frail patients according to our CFFI, significant differences were found. Patients treated with MIT had significantly less major and minor complications compared to ORIF and revision. Furthermore, patients treated with ORIF experienced significantly less minor complications than with revision surgery ( P = .015). Discussion and conclusion: This study shows that frail patients can be adequately detected using our frailty score CFFI and have a lower survival rate, regardless the type of surgery. Another finding is that for frail patients, more invasive surgery has a negative influence on the outcome of the treatment. Therefore, it is of great importance to assess and use the patient’s level of frailty to determine the surgical procedure for a PPF.